Sustainable food consumption: A qualitative study of the factors and motivations influencing the switch in consumer behaviour towards sustainable food consumption in Germany - Mirgeta Hajdari (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2023)
Sustainability can be seen as one of the most important issues of the 21st century and has increasingly moved into the spotlight in Germany, becoming the main topic of discussion today. The growing interest in sustainable food is not only pushing the German food industry to expand its supply of sustainable products to meet the consumer demand, but it also raises the question about what is driving German consumers to adopt a sustainable nutrition lifestyle today more than ever before. Since neither literature nor preliminary data are available to provide information on the causes of this shift in sustainable consumption behaviour in Germany, it has become the subject of the present research work. It attempted to identify certain links between motivation, relevant external factors and the shift in eating behaviour patterns that have contributed to the growing awareness and trend towards sustainability. Regarding this, the theory of consumer behaviour proposes a number of models and explanatory approaches to explain consumer behaviour among which the SOR model provides a suitable explanatory approach to better understand the rising shift in sustainable food consumption as it analyses the consumer's internal processes which is also called the black box. In this way, it was the purpose of the research to open the black box in order to obtain a better understanding of the internal consumers' processes responsible for the decision to adopt a sustainable nutrition. As a result, the research identified a range of motivations, which has been essentially seen as an interplay between intrinsic beliefs and extrinsic drivers. Among these reasons cited were environmental and climate factors, health, wellbeing and altruistic attitudes, ethics and morals, animal welfare, and others. Furthermore, external factors such as the Corona pandemic, social media, media in general, the social environment such as family, friends or colleagues, and others were identified to have played an immediate, influential role and have contributed to the shift towards sustainable food consumption. This paper has also further demonstrated the importance of further research, especially in interdisciplinary areas of sustainable nutrition, and the need to develop applicable approaches for action. This is because planet earth reflects the ways people live today and the time is now to start making a difference in how people live on it - which is why sustainable nutrition offers one of the many ways to accomplish it.
Keywords: 650; sustainability; consumer behaviour; food sector; SOR model; blackbox; factors and motivations; switch and change